Dietary mineral patterns are associated with the pre-diabetes regression and progression: the Tehran lipid and glucose study (TLGS) - Mohammad Jalali; Zahra Bahadoran; Parvin Mirmiran; Fereidoun Azizi (BMC Nutrition)
Abstract Aim We investigated the potential association between dietary mineral patterns and longitudinal change of glycemic status among individuals with prediabetes (Pre-DM). Methods This study included 1456 individuals with Pre-DM (mean age of 47.2 ± 12.8, and 52.5% men) who participated in the third (2006–2008) and fourth (2009–2011) examinations of the Tehran Lipid and Glucose Study (TLGS) that followed up until 2015–2017. The participants’ habitual dietary intakes of minerals were assessed using a semi-quantitative food frequency questionnaire (FFQ) at baseline. Principle factor analysis (PCA) identified three major mineral patterns (with a total variance of 92.3%), including multi-mineral (MM) (characterized by higher loads of phosphorous, zinc, calcium, magnesium, and copper), chromium-selenium (Cr-Se), and iron-manganese (Fe-Mn) patterns. Cox proportional hazard models were used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs) of developing type 2 diabetes (T2D) and regression to normal glucose regulation (NGR) across tertile categories of mineral patterns score. Results After a median follow-up of 5.8 years, the incidence rates of T2D and NGR was 23.8% and 46.8%, respectively. After adjustment of T2D risk score (i.e., composed of age, sex, family history of diabetes, history of gestational diabetes, body mass index, and physical activity level) and dietary confounders, Cr-Se and Fe-Mn patterns were associated with an increased chance of returning to NGR by 26% (HR = 1.26, 95% CI = 1.02–1.55) and 42% (HR = 1.42, 95% CI = 1.14–1.76), respectively. Fe-Mn pattern was also associated with a reduced risk of developing T2D (HR = 0.67, 95% CI = 0.49–0.92). Conclusion Our findings emphasize the potential benefits of dietary Fe-Mn and Cr-Se intakes in pre-diabetic individuals.